2022
DOI: 10.1071/zo21022
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat selection by small mammals in response to fire

Abstract: Understanding how fire influences animal behaviour, such as movement and resource selection, is important for ecosystem management because it can improve our capacity to predict how species will respond. We assessed microhabitat selection by two small mammals, the bush rat (Rattus fuscipes) and agile antechinus (Antechinus agilis), in response to a low intensity prescribed fire. We used spool and line tracking and touch pole vegetation surveys to quantify microhabitat selection along 21 trails for bush rats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 82 publications
1
11
2
Order By: Relevance
“…Our approximate 6-7 m of location error was at the lower end of that range and closely approached the suggested distance of 5 m to maintain accuracy given our study area size (60.7 ha) and relative patch sizes (~ 5-10 ha) [46]. Current in-depth resource selection studies of small mammals using micro-VHF devices are limited and even fewer have detailed telemetry error assessments [1,15,17,23,31,32,76]. Therefore, it was difficult to gauge what distance would create an impactful bias in a small mammal study.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our approximate 6-7 m of location error was at the lower end of that range and closely approached the suggested distance of 5 m to maintain accuracy given our study area size (60.7 ha) and relative patch sizes (~ 5-10 ha) [46]. Current in-depth resource selection studies of small mammals using micro-VHF devices are limited and even fewer have detailed telemetry error assessments [1,15,17,23,31,32,76]. Therefore, it was difficult to gauge what distance would create an impactful bias in a small mammal study.…”
Section: Discussionsupporting
confidence: 56%
“…Because of differences in size, overlap, and perimeter-to-area calculations, different programs identified different dominant cover types or significant changes in percentage of land cover type across the KDE home ranges. While that difference is logical, it is worthy of consideration given the scale of and impact to small mammal resource selection analyses [31,32,76]. For animals that utilize such small spaces, in variable habitats, this could be highly impactful to a study's findings and conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the same token, the burns at both properties may have been of insufficient size or severity to negatively affect the capture rates of Ctenotus grandis and C isolepis, both of which have shown a negative response to fire in previous studies (How & Dell, 2004;Masters, 1996). Low-severity, patchy fires are often promoted as a favorable management approach because they can retain shelter and other resources that allow animals to either persist in recently burned areas or survive until they emigrate to more suitable habitat (Lees et al, 2022;Silveira et al, 1999). There is some evidence to support this for small mammals in tropical savannas (Leahy et al, 2015;Shaw et al, 2021) and temperate woodlands (Swan et al, 2016), but corresponding evidence from arid grasslands is lacking.…”
Section: Burn Size and Severitymentioning
confidence: 99%
“…In response to heightened risk of predation in recently burnt habitat, many prey species alter their habitat use for foraging, resting, and predator avoidance. For example, in the forests of south‐eastern Australia, bush rats avoided burnt vegetation in favour of unburnt patches, increased their use of structurally complex habitat, and made more convoluted movements when foraging (Fordyce et al ., 2016; Lees et al ., 2022). The authors suggested that these behavioural changes were, at least in part, driven by heightened levels of perceived predation risk in burnt forest.…”
Section: What Mechanisms Do Prey Use To Reduce Predation Risk Post‐fire?mentioning
confidence: 99%